What’s algorithms got to do with it? Exploring Black Women’s pursuit of Black love on dating apps - Banks, Jasmine; Monier, Mel; Samuel, Ariana (Discourse, context & media, 2025)
•Black women decode dating app language to gauge partner preferences.•Misogynoir on dating apps adds to the challenge of finding Black love.•Algorithms on dating apps can hinder Black women’s search for love.•Despite existing obstacles, Black women actively seek Black love on dating apps. This study applies intersectionality and Critical Technocultural Discourse Analysis (CTDA) to examine Black women’s experiences with online dating apps and the socio-technical structures that shape their romantic possibilities. While dating apps claim to expand access to romantic connections, their algorithmic systems and user engagement metrics systematically structure desirability hierarchies, reinforcing racial bias and exclusion. Through in-depth interviews with 20 Black women between ages 18 and 30, we explore how Black women define, seek, and experience Black love in digital spaces, revealing the tensions between cultural aspirations for Black partnership and the technological infrastructures that undermine them. Findings show that Black love is not just a personal or cultural ideal but a site of ideological negotiation where algorithmic bias, platform affordances, and broader social hierarchies dictate who is seen, desired, and chosen. Participants describe the emotional labor of self-surveillance, strategic self-presentation, and adaptation, yet many also express doubts about whether Black love is truly possible in spaces designed to marginalize them. Still, they challenge and reimagine Black love, resisting the structures that seek to limit their romantic possibilities. This study contributes to broader conversations on race, technology, and intimacy, urging a critical reassessment of dating apps, especially for Black users.